Pemanfaatan Canva Mobile Dalam Memudahkan Pembuatan Desain Poster dan Brosur - Binanda Wicaksana; Alam Supriyatna; Hardi Jamhur; Lis Utari; Nur Asiah Jamil (LP3M Universitas Binaniaga Indonesia, 2025)
This community service program aimed to enhance the graphic design skills of students at SMK Al-Ikhlas Cisarua Bogor through training using the Canva Mobile application. The implementation method included stages of socialization, intensive training, application of technology in design creation, as well as continuous mentoring and evaluation. During the program, students were introduced to the basics of Canva Mobile, trained to create creative posters and brochures, and encouraged to apply these skills in school activities, such as creating promotional materials for a free health check-up event. The results indicated a significant improvement in students' ability to use Canva Mobile, with most participants producing quality designs that met their needs. The final evaluation revealed that students not only understood the basic features but were also capable of independently developing creative ideas. The program successfully fostered an interactive and collaborative learning environment, boosting students' confidence in using graphic design technology. In conclusion, this training had a positive and tangible impact, with sustainability proposed through the establishment of a graphic design extracurricular activity at the school.